Saúde e gravidez na adolescência nas concepções dos professores de Ciências: uma análise socioepistêmica à luz de Bourdieu - Reis, Alessandra Crystian Engles dos (2021)
This study contextualizes the different health conceptions throughout human history, whose emphasis was on both restricted and broad ones. The restricted conception focuses on biological aspects, while for the extended one, health is understood as a human right, a result of living conditions. Teenage pregnancy has also been observed and analyzed as a biological and social phenomenon that occurs in woman's body. Therefore, sexuality education of a Science teacher was considered as intrinsic to health, and such teacher as well since he/ she traditionally works with Health Education (HE) as a subject. According to this context, it was defined as a research question, 'With which conception of health/disease does the Science teacher understand and address teenage pregnancy in his/her teaching practice?' Thus, this research aimed at identifying and analyzing the conceptions of health/disease of Science teachers, from a Regional Education Center in Western Paraná, based on their teaching practice about teenage pregnancy. This study took place after an approval by the Ethics Committee for Research in Human Beings of the Western Paraná State University – Unioeste, and assent nº 3.200.121. There were 17 teachers, agents of this research, and ten of them answered the online quiz were also interviewed. Based on this qualitative approach study and on Pierre Bourdieu's sociology as a methodological theoretical framework, a Socio-Epistemic Analysis (SEA) was developed in three stages represented by Heuristic Analysis Schemes (A, B and C) with the identification of Analytical Constructs (AC) Field, Habitus, Cultural Capital and Symbolic Violence, by Constructal Indicators (CI) present in the writings and speeches. Thereunto, a priori, three Axes of Thematic Domains were created: 1- Discipline of Science and Health: teenage pregnancy understanding; 2- Health for the Science teacher: broad and restricted conceptions; 3- Health and pregnancy in the context of biopsychosocial relationships among boys and girls from a Science teacher’s viewpoint. It was identified that the restricted conception is structured in the school microcosm, which is influenced by conceptual forces that are external to the field, comprising the person focused on the body, her/his manifestations and relationships. When the Science teacher has the school habitus, he/she has also assumed this concept of health that reinforces the architecture of this field, perceived in his/her relationship with the approach in HE. An adolescent is an agent subdued in various and diverse fields, thus, he/ she experiences some rights with difficulty, since she/ he is a victim of symbolic violence, and also at the school field, with the absence of sexual education. Some apprehensive attempts of ruptures by the Science teacher emerge in the school field, which tend towards a broaden concept of health, in which the citizenship right was sometimes considered. However, sexual education practice is not prestigious in this field, despite it seems to be integrated into the school space. The student, when influenced by the diverse fields that he/she goes through, with emphasis on the familiar one, when full of moralized cultural capital, reproduces the parental logic and contributes to feedback censorship on sexuality, including on its teaching in the school field.